Differences in right ventricular function and response to targeted therapy between patients with IPAH and PAH-CHD - Zhu, Tengteng; Wu, Panyun; Tan, Zhen; Jin, Quan; Chen, Yusi; Li, Lian; Chen, Zewei; Tang, Yirui; Li, Jiang; Fang, Zhenfei (Frontiers in Pharmacology, 2023)
Background and aims: Pulmonary arterial hypertension (PAH) is a chronic pulmonary vascular disorder characterized by elevated pulmonary vascular resistance (PVR) and pulmonary arterial pressure (PAP). Right heart failure is a life-threatening complication of PAH and predicts a poor prognosis. PAH associated with congenital heart disease (PAH-CHD) and idiopathic PAH (IPAH) are two prevalent PAH subtypes in China. In this section, we set out to explore baseline right ventricular (RV) function and its response to targeted agents between IPAH and PAH-CHD. Methods and results: Consecutive patients diagnosed with IPAH or PAH-CHD by right heart catheterization (RHC) in the Second Xiangya Hospital from November 2011 to June 2020 were included. All patients received PAH-targeted therapy and the RV function was assessed by echocardiography at baseline and during follow-up. A total of 303 patients (age, 36.23±13.10 years; women, 213 (70.3%); mean PAP [mPAP], 63.54±16.12 mmHg; PVR, 14.74±7.61 WU) with IPAH (n=121) or PAH-CHD (n=182) were included in this study. Compared with PAH-CHD, patients with IPAH had worse baseline RV function. As of the latest follow-up, forty-nine patients with IPAH and six patients with PAH-CHD died. Kaplan–Meier analyses showed better survival in PAH-CHD versus IPAH. After PAH-targeted therapy, patients with IPAH had less improvement in 6MWD, World Health Organization functional class, and RV functional parameters compared with patients with PAH-CHD. Conclusion: Compared with patients with PAH-CHD, patients with IPAH had worse baseline RV function, unfavourable prognosis, and inadequate response to targeted treatment.